TRANSFORMATION OF SHARIA ECONOMY IN THE POPULIST SYSTEM - Miftahur Rahman; Fathudin Fathudin; Abdul Basit (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research discusses the transformation of sharia economy in the populistsystem. The growth of LKS (Lemabaga Keuangan Syariah) is determined by the strategic role of Indonesia's national development. The most basic national economic problems can be overcome by increasing UMKM / people's economies whose value reaches 99% of the overall onal rice economy. Therefore, it is better to develop sharia / Islamic economy in Indonesia focused on the people's economy, not only on the financial industry sector. The transformation of islamic economy is synergized with the indonesian context of the populist economic system. The basic principles of islamic economic synergy and the populist system are: divinity, justice (social justice), balance (humanity), freedom (deliberation), unity (family), and responsibility.